Phylogenetic patterns in the geographic distributions of birds support the tropical conservatism hypothesis. Issue 11 (8th September 2015) - Duchêne, David A.; Cardillo, Marcel
Abstract Aim Recent research suggests that the latitudinal diversity gradient (LDG) in birds is unlikely to result from faster diversification in the tropics. This puts the focus on other mechanisms, such as dispersal, as the primary drivers for the LDG. We aim to distinguish two prominent models, tropical conservatism (TCH) and out of the tropics (OTM), which make distinct predictions about dispersal across latitudes and the phylogenetic clustering of assemblages in temperate regions. Location Global. Methods We used geographic and phylogenetic data for more than 9000 bird species to reconstruct the ancestral latitudinal zone for each node in each of 100 bird phylogenetic estimates. We used methods that consider discrete latitudinal zones, as well as those that consider latitudinal position as a continuous variable. We then estimated the frequency of ancestor–descendant dispersal within and across latitudinal zones. We also quantified phylogenetic clustering in latitudinal zones separately for bird assemblages within the Old World and the New World. Results Latitudinal distributions are relatively conserved: 60–96% of nodes had the same inferred latitude as their immediate ancestral node. We find that dispersal events out of the tropics were less frequent (4–5%) than dispersal events into the tropics (15–21%), the opposite of what would be expected under the OTM. Nodes with inferred temperate distributions are generally younger than the Eocene–Oligocene Climate Transition, as expected under the TCH. Phylogenetic clustering shows no regular patterns of association with latitude, and is likely to be largely driven by radiations within a few large forested biomes. Main conclusions Our results provide support for the expectations of the TCH, but are less consistent with those of the OTM. Both the deeper origins of tropical clades and the comparatively recent but infrequent dispersal events into temperate regions appear to play a role in generating the strong disparity in tropical and temperate species richness in birds.